The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.17219/dmp/144596
|View full text |Cite
|
Sign up to set email alerts
|

Complications post simple exodontia: A systematic review

Abstract: Exodontia procedures are not without complications, which are the dentist's responsibility to avoid by taking into account clinical, imaging, systemic, and operative factors, among others. The purpose of this systematic review is to determine and analyze the prevalence of complications post simple exodontia (CPES). The method used in this systematic review was adapted from the Cochrane Handbook and PRISMA statement. A systematic search was conducted in PubMed, Scopus and ScienceDirect using the search terms "E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
(70 reference statements)
0
1
0
1
Order By: Relevance
“…Some studies have correlated the reduced electrical activity with clinical signs like maximum mouth opening, and it has been found that in patients with whom there is a faster recovery of the electrical activity to a normal or preoperative value, the recovery is faster concerning the mouth opening and also the reduction of swelling [18]. In this study, it has been found that the electrical activity of the temporalis is higher than that of the masseter muscle measured at all the intervals of the follow-up period, with statistically significant values (p = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have correlated the reduced electrical activity with clinical signs like maximum mouth opening, and it has been found that in patients with whom there is a faster recovery of the electrical activity to a normal or preoperative value, the recovery is faster concerning the mouth opening and also the reduction of swelling [18]. In this study, it has been found that the electrical activity of the temporalis is higher than that of the masseter muscle measured at all the intervals of the follow-up period, with statistically significant values (p = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…If dentists anticipate complica-tions or lack expertise, they should consider referring the patient to a specialist physician to avoid harm. [10][11][12]22,23 The study's results highlight nerve injuries, oroantral fistulas, tooth or root migrations, foreign bodies in bones and anatomical spaces, and jaw fractures as common occurrences during or after tooth extractions.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Even seemingly simple tooth extractions, commonly performed by dental trainees in their third year of education, hold potential complications for patients. [10][11][12] Moreover, improper interventions in the oral and maxillofacial region can lead to rapid and evident consequences, impacting functions such as chewing, speaking, and facial aesthetics (e.g., after jaw fracture treatment or orthognathic surgery), making the results of improper treatments more apparent. 2,3,5,13 Improper medical treatment, considered professional negligence, can lead to additional patient injuries.…”
mentioning
confidence: 99%
“…The adhesive technique utilizes the bonding capability of the adhesive to establish a connection between the enamel surface and the base of the attachment [2].…”
Section: Introductionmentioning
confidence: 99%